1221 Changes in body mass index before and after long-term sick leave due to cancer among workers: j-ecoh study. (24th April 2018) - Kuwahara, K; Endo, M; Nanri, A; Kashino, I; Nishiura, C; Hori, A; Kinugawa, C; Nakagawa, T; Honda, T; Yamamoto, S; Imai, T; Nishihara, A; et al.
Abstract : Introduction: To establish effective supporting system for workers returning from sick leave due to cancer is an emerging global issue. Better understanding of their physical conditions would provide important information to address this issue. However, even simple information, for example, weight reduction by cancer type, is scarce in occupational settings. Here, we report body mass index (BMI) trajectories before and after long-term sick leave due to cancer among workers in Japan. Methods: This is a cohort study among workers in Japan who took sick leave (consecutive 30 days or more) due to cancer between April 2012 and March 2013 and returned to work until March 2014 using data from Japan Epidemiology Collaboration on Occupational Health Study. Follow-up was conducted using annual health examination data until March 2016. Longitudinal data on BMI was extracted from the annual health examination database. BMI trend change before and after sick leave and effect modification by cancer type on the change was estimated using multivariable mixed models. Results: Over 90 000 workers belonged to the participating companies in 2012. One-hundred one workers newly took sick leave due to cancer in 2012. Data on BMI at least two time-points before and after sick leave each were available in 49 workers. Overall, weight reduction occurred after returning from sick leave from cancer (p<0.001). The tendency of weight reduction after returning from sick leave was significantly different by cancer type (p<0.001). Greater weight reduction was observed in esophageal and stomach cancer (n=10). Discussion: We found heterogeneity in weight reduction by cancer type after returning from sick leave due to cancer. The data suggest that occupational health professionals should pay more attention in weight reduction for workers who returned from long-term sick leave due to esophageal and stomach cancer.